Analisis Dampak Pengaruh False Air pada Kenaikan Persentase Oksigen (O2) pada Coal Mill di PT Semen Padang Indarung V - Annisa , Dwi; Parmanaon, Durain; Rahmad, Alfein; Ankarani, Panca (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This research aims to analyze the impact of False Air on the increase in Oxygen (O2) percentage in the Coal Mill at PT Semen Padang Indarung V. False air or unwanted air leakage is a serious problem that can affect the efficiency of Coal Grinding processes and combustion quality in the Kiln. The research was conducted using operational data collection methods over 6 months, including measurements of O2 levels, Mill Temperature, differential pressure, and Grinding Efficiency. The analysis results show a significant correlation between increased False Air and Increased O2 percentage, where every 1% increase in False Air causes a 0.5% increase in O2 levels and a 2% decrease in Grinding Efficiency. Other identified impacts include an Average Mill temperature decrease of 5°C, a 15% increase in ID Fan power consumption, and a reduction in Grinding capacity of up to 10%. The implementation of improvement programs such as seal replacement, Mill housing repair, and ventilation system optimization has been proven to reduce O2 levels to reach the ideal value of 3-4% and increase grinding efficiency. This research contributes to understanding the influence of False Air on Coal Mill performance and can serve as a reference in preventive maintenance programs to prevent air leakage in Coal Mill systems.